Features of the Spatial Spread of Rabies in the Conditions of Mountain RELIEFS of South Siberia (Republic of Altai) - I. D. Zarva; L. D. Shchuchinova; S. A. Chalchikov; A. D. Botvinkin (Эпидемиология и вакцинопрофилактика)
Relevance. The experience of combating rabies in Europe has shown that the tactics of preventive measures in mountains must be modified. At the beginning of the 21st century, the spread of fox rabies into the previously rabies-free mountain areas in southern Siberia was noted. The aim is to trace the spread of rabies in the Altai Mountains after the introduction of the virus. Materials and methods. A retrospective descriptive study using GIS was carried out. For mapping, information on 55 laboratory confirmed cases of rabies in the Altai Republic, QGIS 3.16.0, ArcMap 10.8.1, ArcScene 10.8.1 programs and an electronic landscape-geographical maps "Natural Earth" and "Open street map" were used. The spatial-temporal distribution of rabies was compared with changes in postexposure prophylaxis (PEP). Results. In 2007, rabies was detected for the first time since 1948 in the Altai Mountains. Wild animals (fox, wolf, badger) accounted for 52.7% (95% CI 39.5–65.9). Most of the cases were found in the foothills and river valleys at an altitude of less than 1,000 meters above sea level and only 16.4% (0.0–26.2) – in areas with heights from 1,000 to 2,000 m. Rabies was not recorded in the mountains above 2,000 m. Two different directions of the virus introduction are assumed: from the forest-steppe plains of the Altai Territory (Russia) and from the mountainous steppes of Mongolia. In 2007–2019 the annual number of patients seeking medical attention after animal bites increased by 86%. A correlation between the animal case number in different areas and the average annual PEP was noted (r = 0.649, p = 0.03). 4. Conclusions. Features of the fox rabies spread in the Altai Mountains allows to use the experience of fighting this disease in the mountainous regions of Central Europe.